Recent progress in thermally conductive polymer/boron nitride composites by constructing three-dimensional networks. (April 2021) - Bai, Xue; Zhang, Chengxu; Zeng, Xiaoliang; Ren, Linlin; Sun, Rong; Xu, Jianbin
Abstract: As one of the critical components in thermal management system, high thermally conductive polymer composites is the key factor affecting the heat dissipation of electronic devices. During the past few decades, considerable researches have been done to enhance the thermal conductivity of polymer composites by adding fillers with high thermal conductivity, such as metals, carbon-based materials and ceramics. Boron nitride (BN) has been considered as an ideal thermally conductive filler for polymer composites. However, the large interfacial thermal resistance at the filler-matrix interfaces and the filler-filler interfaces has greatly hampered the heat conduction, resulting in the limited improvement in thermal conductivity. In this mini review, we attempt to present recent progress in fabricating high thermally conductive polymer/boron nitride composites by constructing three-dimensional networks. We started from introducing the thermal conduction mechanism in polymer composites, and then briefly discussed the factors influencing the thermal conductivity of polymer composites, followed by presenting different fabrication methods of constructing three-dimensional networks in polymer/boron nitride composites to increase the thermal conductivity. We hope this mini review would provide some beneficial inspiration for improving the thermal conductivity of polymer composites. Graphical abstract: Image 1 Highlights: We present recent progress in fabricating high thermally conductive polymer/boron nitride composites. Including: The mechanism of thermal conduction in polymer composites. The factors affecting the thermal conductivity of polymer composites. The fabrication methods of thermally conductive polymer/boron nitride composites with three-dimensional networks.